2010
DOI: 10.1007/s10562-010-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Cu:Al Nano Catalyst for Selective Hydrogenolysis of Glycerol to 1,2-Propanediol

Abstract: Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H 2 pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu ? species in the activated Cu:Al nano catalyst. Although Cu ? is catalytically inactive in glycerol hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 31 publications
3
76
0
3
Order By: Relevance
“…A similar deactivation pattern was observed for Cu/Al 2 O 3 catalysts [11]. Few catalysts have been demonstrated to be both active and stable towards glycerol hydrogenolysis in aqueous media [13][14][15][16]. Recently, Ga 2 O 3 -modified Cu/ ZnO catalysts have exhibited an enhanced stability, even after four consecutive glycerol hydrogenolysis reactions at 493 K, without apparent deactivation [16].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…A similar deactivation pattern was observed for Cu/Al 2 O 3 catalysts [11]. Few catalysts have been demonstrated to be both active and stable towards glycerol hydrogenolysis in aqueous media [13][14][15][16]. Recently, Ga 2 O 3 -modified Cu/ ZnO catalysts have exhibited an enhanced stability, even after four consecutive glycerol hydrogenolysis reactions at 493 K, without apparent deactivation [16].…”
Section: Introductionsupporting
confidence: 61%
“…Until now, supported Cu [3], Co [4], Ni [5], Ru [6], Pt [7], Rh [8] and Ir [9] catalysts have been reported to be active towards glycerol hydrogenolysis. However, the sintering of the metal particles during the course of the reaction often resulted in catalyst deactivation [10][11][12][13]. For example, the sintering of Cu particles in the Cu/ZnO catalysts reduced the conversion of glycerol from 46 to 10% upon reuse [10].…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of glycerol to 1,2-PDO has been extensively studied in recent years, and high yields have been obtained in previous reports [8,9,[13][14][15][16][17][18][19][20][21][22]. In contrast, direct hydrogenolysis of glycerol to 1,3-PDO is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Mane and coworkers reported that a non-chromium Al-Cu nano-sized catalyst showed higher catalytic activity compared to two commercial copper chromate catalysts. 30 For aqueous-phase hydrogenolysis of glycerol, the conversion could be increased up to 76% at 513 K, while a high 1,2-PD selectivity of 89% was maintained. The highest activity of this nanocatalyst could be attributed to the higher acidic sites because the aluminium present in this catalyst can be converted to alumina during the calcination process, which is generally responsible for higher acidity leading to faster dehydration to form acetol.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%